2005
DOI: 10.1021/ja053134r
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mesopores in Intracrystalline Transport in USY Zeolite:  PFG NMR Diffusion Study on Various Length Scales

Abstract: PFG NMR has been applied to study intracrystalline diffusion in USY zeolite as well as in the parent ammonium-ion exchanged zeolite Y used to produce the USY by zeolite steaming. The diffusion studies have been performed for a broad range of molecular displacements and with two different types of probe molecules (n-octane and 1,3,5-triisopropylbenzene) having critical molecular diameters smaller and larger than the openings of the zeolite micropores. Our experimental data unambiguously show that, in contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
188
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(203 citation statements)
references
References 23 publications
12
188
1
2
Order By: Relevance
“…On the other hand, it has been recognized that the extent to which mass transport is improved is highly dependent on the "quality" of meso-(or macro-) pores, as mesopores can enhance mass transport only if they are connected with the exterior surface of zeolite crystals 12b, 14a, 15 . Weitkamp et al 16 have observed that the presence of intracrystal mesopores in USY has virtually no impact on mass transport, a phenomenon that . It is therefore desirable to find ways that can produce HPZs with small primary particle size that can shorten the diffusion pathway, and at the same time keep the mesopores connected to the external surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been recognized that the extent to which mass transport is improved is highly dependent on the "quality" of meso-(or macro-) pores, as mesopores can enhance mass transport only if they are connected with the exterior surface of zeolite crystals 12b, 14a, 15 . Weitkamp et al 16 have observed that the presence of intracrystal mesopores in USY has virtually no impact on mass transport, a phenomenon that . It is therefore desirable to find ways that can produce HPZs with small primary particle size that can shorten the diffusion pathway, and at the same time keep the mesopores connected to the external surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, M41S materials generally exhibit weak acidity and low hydrothermal stability due to their amorphous frameworks. As a consequence, new synthesis strategies have been developed to obtain materials which com-bine the advantages of mesoporous materials and those of zeolites [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. For example, Corma et al [21] reported a post-synthesis dealumination process via steaming or acid leaching on full-grown zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main drawbacks of this method is that the Brønsted acidity of the zeolite material is severely affected, and the materials may thus become less suitable for acid-catalyzed reactions. Moreover, it has been demonstrated that this postsynthesis modification treatment most often leads to encapsulated porosity, [12,13] which is not readily accessible and, therefore, only contributes to the improved diffusion in a limited way.…”
Section: Introductionmentioning
confidence: 99%